Corrigendum: Real-time effects of lateral positioning on regional ventilation and perfusion in an experimental model of acute respiratory distress syndrome - Mlček, Mikuláš; Borges, João Batista; Otáhal, Michal; Alcala, Glasiele Cristina; Hladík, Dominik; Kuriščák, Eduard; Tejkl, Leoš; Amato, Marcelo; Kittnar, Otomar (Frontiers in physiology, 2023)
[This corrects the article DOI: 10.3389/fphys.2023.1113568.].
Keywords: ventilator-induced lung injury; mechanical ventilation; body position changes; lung collapse; acute respiratory distress syndrome